Effects of Temperature, Molecular Weight, and Non-Solvent Variation on the Physical Properties of PVDF Membranes Prepared through Immersion Precipitation - Resa Wulandari; Edi Pramono; Sun Theo Constan Lotebulo Ndruru; Abu Masykur; Sayekti Wahyuningsih; Aditya Muhammad Fadhilah; Ellya Syaharani; Elva Yoga Saputra; Mayzy Vanesia Insani (Jurnal Kimia Sains dan Aplikasi, 2024)
Research on porous membrane technology is proliferating, especially in the process of fabrication of membranes. Different methods in membrane fabrication can affect the physical and chemical properties of the produced membrane. This study aims to investigate the influence of temperature, molecular weight, and non-solvent type on the physical-chemical properties of PVDF membranes. The membrane was produced by the immersion precipitation method with varying PVDF molecular weights of 64 kDa, 352 kDa (Solef 1010), 534 kDa, and 573 kDa (Solef 1015); non-solvent variations of alcohol (methanol, ethanol, isopropyl alcohol, and butanol); and drying temperature variations of 40, 50, and 60°C. The produced membranes were analyzed using ATR-FTIR, XRD, TGA, DSC, and SEM, and their wettability properties were evaluated using water contact angles. The optimal drying temperature for membrane production was 60°C. The ATR-FTIR data showed that molecular weight impacted membrane structure, where PVDF MW 534 kDa membrane had the highest percentage of β phase (77.47%). Non-solvent changes also affected membrane structure; PVDF Solef 1010 with non-solvent isopropyl alcohol had the highest percentage of β phase (67.45%). This is supported by the XRD diffractogram that displayed peaks at 2θ values between 20.24° and 20.66°, indicating the presence of a phase β PVDF. The thermal analysis exhibited three stages of degradation for Solef 1010 with ethanol non-solvent and two for the other seven membranes. The degradation temperature increases with the increase in molecular weight and the difference in non-solvents. The highest thermal stability membrane was PVDF Solef 1010 with isopropyl alcohol non-solvent (430°C). SEM images showed the membrane with non-solvent isopropyl alcohol, displaying a dense sponge-like morphology. The wettability of membranes is affected by molecular weight and non-solvent type. The membrane with isopropyl alcohol non-solvent obtained the smallest contact angle (54.77°) and indicated the most wettability membrane.